Lower Limits and Nonlinearity of Calibration in Suppressed Ion Chromatography with Strong Acid Eluent. (30th July 2015) - Eom, Jiwon; Kim, Mi‐Young; Lee, Bokyoung; Lee, Dong Soo
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" id="bkcs10407-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> Chromatograms of Li+ standard solutions at (a) 11, (b) 51, (c) 76, and (d) 123 μg/L, respectively, showing Li negative peaks and non‐lineare response.